Shakespeare translation in Japan: 1868—1998 - Akiko Sano (Ilha do Desterro)
Shakespeare was first introduced to Japan in the late nineteenth century, when the country opened its doors to other countries after the seclusion policy of over two hundred years. When the Meiji Restoration Government came into power in 1868, it decided to import the Western culture and technology in order to catch up with the developed countries. Japan’s overall contact with the Western world began. The country’s slogan then became “civilization and enlightenment”, which meant Westernization for “national wealth and military strength”. Shakespeare came to Japan together with other things from Britain during this age of Westernization. The translation of two English books were published in 1871 and 1872 to enlighten the youth of the new age. One was Samuel Smiles’ Self-Help (1859) and the other was John Stuart Mill’s On Liberty (1859). Both books acquired immediate popularity. The translator was Masanao Nakamura who was originally sent by the old Tokugawa Government to Britain to study English.